Collaborative Problem-based Learning: An Analysis of Problem-Solving Skills in Vocational Schools - Rachmad Syarifuddin Hidayatullah; Sudirman Rizki Ariyanto; Muhaji; Husni Mubarok; Abebayehu Yohannes (IJORER : International Journal of Recent Educational Research, 2020)
This study aims to analyze the effect of using Collaborative Problem-Based Learning (CPBL) on students' problem-solving skills. This study used a 2x2 factorial design, in which the selection of experimental and control groups was determined with convenience sampling. The data analysis technique of this research is divided into two types, namely the prerequisite analysis test and hypothesis testing. The findings of this study concluded that students who studied with CPBL had significantly higher problem-solving skills than students who studied with Direct Instruction (DI). In addition, high problem-solving skills were generally owned by students with high initial skills. Meanwhile, the complete the results of the hypothesis test this study also showed a significant interaction between the learning model and initial skills on students' problem-solving skills in internal combustion motor competences. This shows that the selection of the right learning model is needed according to the initial skills of students so that problem-solving skills can be adequately developed. Thus, it is hoped that vocational school students can become graduates who can compete in the world of work.